Effects Cuminum cyminum Extracts in Lipid Profile Levels and Internal Tissues of Infected Balb/c Mice with Hydatid Cysts - Maroof Sabti Juma Al-Ammash (Journal of Global Pharma Technology, 2018)
Hydatidosis is one of the most cosmopolitan zoonotic disease that may causes death and still very common in the developing world. The present study aimed to detect the effects of Albendazole and C. cyminum extracts on lipid profile, liver and spleen of infected Balb/c mice with hydatidosis. This study showed positive results for tannins, phenolic compounds, flavonoids and glycosides in alcoholic and aqueous extracts of C. cyminum, while negative result for alkaloids. Significant (p ≤ 0.05) increasing of total cholesterol was detected for the third (273.57 mg/dl) and fourth (281.73 mg/dl) positive control groups. Triglycerides shows significant increasing in groups 3 (248.65 mg/dl) and 4 (260.30 mg/dl) of positive control groups. About HDL-C, significant decreasing was recorded in the third and fourth positive control groups (40.87 mg/dl and 33.42 mg/dl, respectively), while significant (p ≤ 0.05) elevation was occurred for HDL-C in Albendazole treatment group (60.87 mg/dl) as compared with the negative control group, with no significant differences were reported for HDL-C in alcohol and aqueous extract treated groups. For histological study, the present study showed degeneration of hepatocytes, thickening wall of hepatic blood vessels and infiltration of lymphocytes for Albendazole treatment group, while alcoholic and aqueous extract treated groups showed central vein, hepatocytes and sinusoids with normal sizes. Concerning spleen, results in the current study showed normal shape and size for white pulp, red pulp and central artery of all treatment groups, while edema and necrotic materials appeared in some of positive control groups.Keywords: Hydatidosis, Hydatid cyst, Cuminum cyminum extract Histological effects.